PROYEK ANGGARAN SEBAGAI ALAT PENGENDALIAN BIAYA PADA KANTOR SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH IV PROVINSI NUSA TENGGARA TIMUR - Maria Yunita Ina; Lambertus Langga (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
This study aims to determine and analyze whether the difference that occurs is a favorable difference for the Janction Kelimutu Ende road project and to determine the function of the project budget plan as a cost control tool for the Janction Kelimutu Road project at the Regional National Road Implementation Unit Office IV East Nusa Tenggara Province. The method used in this research is quantitative research which emphasizes on resting the project method. The analytical method used in this research is variance analysis. The results in this study, namely (1) there is a difference between the budget and the realization of the cost of the road widening project at the Kelimutu Ende Junction; (2) the function of the protection budget made by the company has not functioned properly as a control tool,; and (3) the form of control carried out by the management as a result of an unfavorable difference between the budget and the realization of project costs, namely by conducting periodic supervision.